Bumi Sakinah Foundation’s Teacher and Administrative Staff Planning Management - Muhammad Sholihuddin (Nalar Global Foundation, 2021)
The purpose of this study was to determine the planning management of educators and education personnel at the Bumi Sakinah Foundation, Batam. This research is a qualitative descriptive type, namely research based on post-positivism philosophy. Collecting data using observation, interviews and documentation. The results of this study explain that 1) The planning management of educators and education staff at the Bumi Sakinah Foundation Batam can be categorized as good. With a lot of evidence that validates the research data. The existing Renstra (Strategic Plan) has met the planning standard which has a process and evaluation in every strategic plan that is carried out. Although there are several things that need to be improved and continue to be evaluated for the progress of the Bumi Sakinah Foundation Batam, and especially for Islamic religious education today. And the cohesiveness of the leaders and members is very good, so that it creates a positive aura in the learning process at school and can compete in the realm of education. 2) external factors in the planning of educators and education personnel are the weaknesses of the school's vision and mission, curriculum, work programs, education funds, quality of teachers and students, learning facilities and media, school infrastructure, principals, leadership, school environment planning, activities academic and non academic and discipline. Then internal factors can be divided, namely competition between schools, and the development of Science and Technology.